Innovation Strategy Of Improving Brilliant English Course Business - Putri, Amelia Kusumaning; Muslih, Basthoumi (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The aim of this research is exploring and the propose effective open inovation stragtegies for Brilliant English Course to enhance its curriculum, integrate modern technologies, personalize learning experiences, expand its market reach, and student satisfaction. Design/Methode/Approach :the research will adopt a qualitative approach, utilizng case study analysis, interviews and documentation. The selection of informants used the 5R (Realize, Relevance, Recommendation, Report, Readiness). Research Finding : The integration of Al Driven platforms and Online learning management systems to provide personalized and flexible learning experiences. The Development of a Specialized Curicullum, Idenification of potential Partnerships and collaborations with universities, marketing strategies and sustainabel practices , explore open business models for potential Brilliant English Course. Theoretical contribution/Originality :This research will contribute to the existing body of knowledge on Open Innovation by applying it to the context of educational institutions, specifically language institute. The originality of this research lies in its focus on integrating both technological advancements and external partnerships within the educational environment, creating a holistic approach to business growth and innovation in education. Practitionel/Policy implication : The research will motivate other institute to grow up better by open innovation strategy. Research limitation : This research focuses only on a The findings are more applicable to Brilliant English Course implementing technologies digital platforms requires significant investment, which might be challeging for smaller institutions.